Telehealth group intervention for adolescents and young adults with cancer: a feasibility pilot study protocol - Sherilynn F. Chan; Joanna Patten; Nancy Lau (Pilot and Feasibility Studies)
Abstract Background Providing opportunities for social interaction and access to psychosocial interventions are 2 of the 15 Standards for Psychosocial Care for Children with Cancer and Their Families. Peer relationships are especially important among adolescents and young adults (AYAs), and cancer disrupts this aspect of social development. Many AYAs with cancer report a desire to engage in peer support groups; however, this remains a critical unmet need. Telehealth is a cost-effective and increasingly common modality for delivering health care that reduces access barriers and may be an especially good fit for AYAs with cancer. Little work has evaluated the feasibility and acceptability of peer support groups for AYAs with cancer. The purpose of this study is to evaluate the feasibility and acceptability of a telehealth peer support group intervention for AYAs with cancer. Methods Telehealth group interventions are offered twice yearly as standard of care at Seattle Children’s Hospital to AYAs on or off treatment for cancer or a brain tumor. Group members are assigned to a High School Group (grades 9–12) or an AYA Group (spring of grade 12 or older). Aim 1 is to determine the feasibility and acceptability of the intervention for all patients who participate in groups in their clinical care. Feasibility will be assessed based on a priori metrics (enrollment, attendance, attrition) for all group members. Group and telehealth acceptability will be assessed by a 16-item internally developed measure that was adapted from the Client Satisfaction Questionnaire. Aim 2 is to conduct patient stakeholder semi-structured interviews post-intervention with 20 AYAs to gather feedback and inform intervention refinement. Participants who opt-in for study procedures will also complete exploratory measures of social connectedness/isolation, depression, and benefit finding, pre- and post-intervention (Aim 3). Discussion Findings from this pilot study will inform intervention refinement, intervention implementation, and sample sizes for future powered trials. This study will provide preliminary empirical evidence to support the development of effective group interventions for AYAs with cancer that increase opportunities for social interaction and access to peer support, with the potential to contribute to improved psychosocial care of AYAs with cancer.